PELATIHAN DIGITALISASI PADA DESA WISATA LOMBOK INDONESIA - Fetty Poerwita Sary; Dian Indiyati; Milleniartha Moslem (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The outbreak of the Covid 19 pandemic had a major impact on Indonesia's economic growth. One of the sectors affected is tourism. To boost the tourism industry, we must not forget the Small and Medium Enterprises (SME) which are one of its supporters. During this pandemic, as many as 75% of SMEs had experienced a significant decline in sales. Most of these business actors apparently do not have a planning strategy for dealing with a disaster (disaster preparedness plan). In fact, this capability can help them prepare for business sustainability both during and after the pandemic. Therefore, the aim of this community service is to increase the empowerment of SME’s HR in order to improve the welfare of community-based tourism in Yogyakarta and Lombok. In general, the stages of activity are divided into two, namely 1) mapping SME’s entrepreneurs; 2) implementation of the online and offline training and mentoring program on entrepreneurial competence. The output expected from this activity is to select young entrepreneurs from each region who will later be given the opportunity to follow pitching and match making events with angel capital (entrepreneurs, CSR, local government, or banking). Meanwhile, the results of this activity are independent entrepreneurs who can become the driving force in their community